The ecology of invasions by Pinus (pinaceae) and Hakea (proteaceae) species, with special emphasis on patterns, processes and consequences of invasion in mountain fynbos of the southwestern Cape Province, South Africa - Richardson, David Mark (Department of Biological Sciences, 2016)
The fire-prone mountain fynbos of the southwestern Cape Province of South Africa has been severely invaded by introduced trees and shrubs. These invasions have transformed fynbos shrublands to dense thickets of trees and shrubs in many parts of the region, thus disrupting various natural ecosystem processes. The ecology of invasions by species of Pinus and Hakea (the most successful genera) was studied using a series of natural experiments in conjunction with autecological studies. The study was divided into main four parts: (i) case studies to elucidate major patterns and processes of invasion; (ii) studies of the life history and population ecology of selected invaders; (iii) studies of the determinants of invasibility; and (iv) assessments of the consequences of invasion and of control programmes. Bibliography: pages 235-272.